2020
DOI: 10.3390/antiox9111065
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation, Peripheral Signals and Redox Homeostasis in Athletes Who Practice Different Sports

Abstract: The importance of training in regulating body mass and performance is well known. Physical training induces metabolic changes in the organism, leading to the activation of adaptive mechanisms aimed at establishing a new dynamic equilibrium. However, exercise can have both positive and negative effects on inflammatory and redox statuses. In recent years, attention has focused on the regulation of energy homeostasis and most studies have reported the involvement of peripheral signals in influencing energy and ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 69 publications
3
21
0
Order By: Relevance
“…Excessive training and effort could lead to chronic fatigue and muscle damage, with lower performance. Therefore, these adaptive mechanisms are the result of a fine balance between: (i) oxidative stress/inflammation induced by exercise that increases performance and health, and (ii) oxidative stress due to excessive effort that causes fatigue and muscle damage [ 2 ]. In this context, the role of oxidative stress and hormone signalling linked to inflammation appears to be crucial for adaptation [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Excessive training and effort could lead to chronic fatigue and muscle damage, with lower performance. Therefore, these adaptive mechanisms are the result of a fine balance between: (i) oxidative stress/inflammation induced by exercise that increases performance and health, and (ii) oxidative stress due to excessive effort that causes fatigue and muscle damage [ 2 ]. In this context, the role of oxidative stress and hormone signalling linked to inflammation appears to be crucial for adaptation [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, these adaptive mechanisms are the result of a fine balance between: (i) oxidative stress/inflammation induced by exercise that increases performance and health, and (ii) oxidative stress due to excessive effort that causes fatigue and muscle damage [ 2 ]. In this context, the role of oxidative stress and hormone signalling linked to inflammation appears to be crucial for adaptation [ 2 ]. Elite athletes have a very strong antioxidant defence system that guarantees free radical detoxification during acute exercise and recovery and, at the same time, the regulation of several hormones ensures adaptation [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…In elite athletes, there is large disparity among different training protocols and the effects on oxidative stress and inflammatory cytokines are still not well known. In a previous review, we concluded that chronic training seems to be responsible for some perturbations in different metabolic hormones linked to inflammation and to plasma redox homeostasis [ 1 ]. Therefore, the correct training program is essential.…”
Section: Introductionmentioning
confidence: 99%
“…Prolonged intense physical activity could increase muscle damage that, in professional athletes, could lead to perturbations in several metabolic hormones related to inflammation. Adiponectin is a signaling hormone with an anti-inflammatory effect and its plasma level is modified by training [ 1 ]. Several studies conducted in women reported a high level of plasma adiponectin compared with men, as well as a positive correlation seen between circulating adiponectin and whole-body insulin sensitivity in women [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Biochemical markers of muscle damage and inflammation are usually monitored to study and optimize recovery after exercise. Creatine kinase (CK) and lactate dehydrogenase (LDH) are two of the most common markers of direct muscle damage [1,6,7] and, according to Nowakowska et al [8], CK and LDH together with aspartate aminotransferase and creatinine levels could constitute a useful set of markers for monitoring recovery periods in soccer players. Among the large number of biochemical markers of inflammation, interleukin-6 (IL-6) and C-reactive protein (CRP) are two of the most frequently used in sport [5,6,7].…”
Section: Introductionmentioning
confidence: 99%